Feasibility of Implementing a Family-Based Inpatient Program for Adolescents With Anorexia Nervosa: A Retrospective Cohort Study - Spettigue, Wendy; Norris, Mark L.; Douziech, Ingrid; Henderson, Katherine; Buchholz, Annick; Valois, Darcie D.; Hammond, Nicole G.; Obeid, Nicole (Frontiers in Psychiatry, 2019)
Background: Manualized Family Based Therapy (FBT) is the treatment of choice for adolescent anorexia nervosa, but it is an outpatient treatment. Very little research has examined whether or how the principles of FBT might be successfully adapted to an inpatient setting, and there is little other evidence in the literature to guide us on how to best treat children and adolescents with eating disorders while in hospital. This paper describes and provides treatment outcomes for an intensive inpatient program that was designed for the treatment of adolescents less than 18 years of age with severe eating disorders, based on the principles of Family Based Therapy (FBT). Each patient’s family was provided with FBT adapted for an inpatient setting for the duration of the admission. Parents were encouraged to provide support for all meals in hospital and to plan meal passes out of hospital. Methods: A retrospective cohort study was conducted that examined the outcomes of 153 female patients admitted over a 5 year period. Outcome data focused primarily on weight change as well as psychological indicators of health (i.e. depression, anxiety, eating disorder psychopathology). Results: Paired t-tests suggest that in addition to weight gain, patients showed improvements in scores of mood, anxiety, and eating disorder psychopathology, though they continued to display high rates of body dissatisfaction and some ongoing suicidality at the time of discharge. Conclusion: This study shows that a specialized inpatient program for adolescents with severe eating disorders that was created using the principles of FBT and which utilizes a combination of individual, group and ‘FBT’-informed family therapy, results in positive short-term medical and psychological improvements as evidenced by improved weight gain and decreased markers of psychological distress.